Polyadenylated versions of small non-coding RNAs in Saccharomyces cerevisiae are degraded by Rrp6p/Rrp47p independent of the core nuclear exosome - Anusha Chaudhuri; Soumita Paul; Mayukh Banerjea; Biswadip Das (Microbial Cell, 2024)
In Saccharomyces cerevisiae, polyadenylated forms of mature (and not precur-sor) small non-coding RNAs (sncRNAs) those fail to undergo proper 3-end mat-uration are subject to an active degradation by Rrp6p and Rrp47p, which does not require the involvement of core exosome and TRAMP components. In agreement with this finding, Rrp6p/Rrp47p is demonstrated to exist as an exo-some-independent complex, which preferentially associates with mature poly-adenylated forms of these sncRNAs. Consistent with this observation, a C-terminally truncated version of Rrp6p (Rrp6p-ΔC2) lacking physical association with the core nuclear exosome supports their decay just like its full-length ver-sion. Polyadenylation is catalyzed by both the canonical and non-canonical poly(A) polymerases, Pap1p and Trf4p. Analysis of the polyadenylation profiles in WT and rrp6-Δ strains revealed that the majority of the polyadenylation sites correspond to either one to three nucleotides upstream or downstream of their mature ends and their poly(A) tails ranges from 10-15 adenylate residues. Most interestingly, the accumulated polyadenylated snRNAs are functional in the rrp6-Δ strain and are assembled into spliceosomes. Thus, Rrp6p-Rrp47p defines a core nuclear exosome-independent novel RNA turnover system in baker’s yeast targeting imperfectly processed polyadenylated sncRNAs that accumu-late in the absence of Rrp6p.